Four new and three redescribed species of the cockroach genus Margattea Shelford, 1911 (Blattodea, Ectobiidae, Pseudophyllodromiinae) from China - Wang, Jinjin; Li, Xinran; Wang, Zongqing; Che, Yanli (Zootaxa, 2014)
Four new species of Margattea Shelford from China are described: M. angusta sp. n., M. flexa sp. n., M. spinosa sp. n. and M. pseudolimbata sp. n.. Male genitalia are illustrated. M. limbata and M. hemiptera are redescribed and illustrated based on types. M. bisignata is described in detail for the first time. A key to Margattea spp. from China and photographs of M. mckittrickae and M. spinifera in nature are provided.